Pengaruh E-Service Quality Aplikasi Grabcar Airport terhadap Kepuasan Penumpang Pesawat di Bandar Udara Sultan Aji Muhammad Sulaiman Sepinggan Balikpapan - Helda Rusiana; Amelia Puspa Tamara (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The shift in services from conventional methods toward digital ones has been driven by rapid advances in information and communication technology, and the online transportation sector is no exception. This phenomenon is evident in the operation of GrabCar Airport at Sultan Aji Muhammad Sulaiman Sepinggan Airport in Balikpapan, which is required to maintain electronic service quality (e-service quality) in order to meet user satisfaction and expectations. Therefore, this study was designed to analyze the impact of e-service quality in the GrabCar Airport app on the satisfaction levels of airline passengers at that airport. A quantitative approach was applied in this study, where the sample was determined using purposive sampling (a type of non-probability sampling) with a total of 100 respondents. Data were collected through the distribution of questionnaires and then analyzed using SPSS 25 software. The data analysis stages included validity and reliability tests, descriptive statistical analysis, classical assumption tests, multiple linear regression, t-tests, F-tests, and analysis of the coefficient of determination. The research findings indicate that, to some extent, the aspects of e-service quality—including reliability, privacy, responsiveness, compensation, and contact—have a significant impact on customer satisfaction. Conversely, the aspects of efficiency and fulfillment do not show an individual effect. However, simultaneous testing indicates that all dimensions of e-service quality (efficiency, reliability, fulfillment, privacy, responsiveness, compensation, and contact) collectively influence passenger satisfaction.